PENGEMBANGAN USAHA KECIL MENENGAH BERBASIS 4.0:FESYEN XUSHA DI KOTA BANDUNG ERA PANDEMI COVID – 19 - Taufik, Taufik; Afriantari, Rini (Indonesian Community Service and Empowerment Journal (IComSE), 2023)
Small and medium enterprises in Indonesia are one of the cornerstones of a new developing economy, including Indonesia. Many creative young people develop various businesses by looking at the times and market needs. Bandung, or Paris Van Java, is a tourist destination famous for its "contemporary" youth fashion. Many young generations (millennials) work and innovate by seeing business opportunities, including the fashion industry. They select and project segments for their products, but their business stagnates due to several constraints. Ruri Erika started a clothing business with a young women segment named Xusha, and she hopes to contribute to Indonesian fashion. Erika designed Xusha products to give young women and young people new colors to look fashionable. However, since the Covid-19 pandemic, government policies to limit community activities have impacted sales of Xusha products. It happened because, before the status of the Covid-19 pandemic, Xusha only relied on marketing through bazaars and exhibitions. The team implemented the PKM FISIP Unpas to assist partners in overcoming various obstacles faced during the Covid-19 pandemic, especially marketing and finance. The program's methods are training and technical guidance approach; this PKM program was implemented from March 27, 2021, to June 6, 2022, successfully providing an understanding of using the Cash Book application to manage financial flows. In addition, the PKM team helps partners carry out promotional and marketing strategies using media through e-commerce and social media.